1986
DOI: 10.1152/ajprenal.1986.251.4.f594
|View full text |Cite
|
Sign up to set email alerts
|

Distinct localization of atrial natriuretic factor and angiotensin II binding sites in the glomerulus

Abstract: A comparative study of the localization of 125I-labeled atrial natriuretic factor (ANF) and 125I-labeled angiotensin II (ANG II) binding sites in the glomerulus of the rat, after an intravascular injection, has been done by ultrastructural radioautography. 125I-ANF binding sites are localized predominantly on the podocytes of the visceral epithelium (63%) followed by the endothelium of capillaries (14%), the parietal epithelium (13%), and finally mesangial cells (10%). In a comparative study, it was confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Although previous ultrastructural autoradiographic studies have not shown a high density of Ang II receptors in afferent and efferent arterioles after intravascular injection of 1251-Ang II (70,71,87), radioligand binding assays in isolated preglomerular resistant vessels have identified high affinity Ang II receptors in normotensive rats (88) and in spontaneously hypertensive rats (86). Binding competition studies with the subtype selective antagonists losartan and PD 123319 indicate a majority of AT1 receptors (> 80% to 90%) with a small proportion of PD 123319-sensitive AT2 sites in these isolated vascular membranes (86,88).…”
Section: Ang II Receptor Subtypes In Renal Vasculaturementioning
confidence: 74%
See 1 more Smart Citation
“…Although previous ultrastructural autoradiographic studies have not shown a high density of Ang II receptors in afferent and efferent arterioles after intravascular injection of 1251-Ang II (70,71,87), radioligand binding assays in isolated preglomerular resistant vessels have identified high affinity Ang II receptors in normotensive rats (88) and in spontaneously hypertensive rats (86). Binding competition studies with the subtype selective antagonists losartan and PD 123319 indicate a majority of AT1 receptors (> 80% to 90%) with a small proportion of PD 123319-sensitive AT2 sites in these isolated vascular membranes (86,88).…”
Section: Ang II Receptor Subtypes In Renal Vasculaturementioning
confidence: 74%
“…The cellular distribution of Ang II receptor subtypes in the glomerulus shows AT1 receptors almost exclusively in mesangial cells, but not in the cells of epithelium, basement membranes, or capillary endothelium (70)(71)(72)(73). In situ hybridization studies using an AT1 receptor riboprobe have identified AT1 receptor mRNA in rat glomeruli, presumably in mesangial cells and the vascular pole (65,68).…”
Section: Ang II Receptor Subtypes In Glomerular Mesangiummentioning
confidence: 99%
“…Podocytes express both AT1 and AT2 receptors that provide high-affinity binding sites for Ang II (7)(8)(9)(10)(11)(12)(13). Administration of exogenous Ang II or targeted overexpression of AT1 to glomerular podocytes resulted in albuminuria and focal segmental glomerular sclerosis in mice (4,8,14,15).…”
mentioning
confidence: 99%
“…9 This observation provides biochemical support for the renal cellular nature of the Wilms' tumor, which is characterized histologically by the presence of preglomerular and pretubular structures 10 and therefore should have contained ANF responsive cells. 4 - 7 The hKT cells depicted in Figure 1 show a spherical epithelial morphology comparable with that depicted for the parent cell line SK-NEP-1. 9 Taken together, the data in the present report suggest that this Wilms' tumor cell line possesses cells that exhibit properties expected of ANF responsive target cells, and thus this cell line may serve as a useful in vitro model for investigating ANF-mediated events at a cellular level.…”
Section: Resultsmentioning
confidence: 70%
“…The most likely second messenger for ANF is cyclic guanosine monophosphate (cGMP). 3 Either ANF binding or stimulation of cGMP formation has been demonstrated in a variety of renal structures including glomerular visceral podocytes, 4 capillary endothelial cells, 4 mesangial cells, 5 cells of the cortical collecting tubule, 6 and juxtaglomerular cells. 7 Increased cGMP accumulation results from ANF stimulation of a membrane-associated guanylate cyclase 3 although ANF inhibition of adenylate cyclase has also been reported.…”
mentioning
confidence: 99%